2010
DOI: 10.1177/00333549101250s412
|View full text |Cite
|
Sign up to set email alerts
|

The Context of Economic Insecurity and its Relation to Violence and Risk Factors for HIV among Female Sex Workers in Andhra Pradesh, India

Abstract: SYNOPSISObjective. We examined the context of economic insecurity and debt among female sex workers (FSWs), how this context varies among FSWs, and its association with experiences of violence and sexual risk factors for human immunodeficiency virus (HIV).Methods. We recruited FSWs aged $18 years (n5673) through respondentdriven sampling for a survey on HIV risk in this region. Using logistic regression models (adjusted for partner status, education, financial support, and literacy), we assessed the relation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
125
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(131 citation statements)
references
References 18 publications
5
125
1
Order By: Relevance
“…Research shows that socioeconomic conditions often underlie entry into sex work and that economic vulnerability can increase HIV-related risks by reducing women's negotiating power with clients and increasing unprotected sex in exchange for more money. 34,35 FSW-PWID who earn less income may be more vulnerable overall and deeply entrenched in drug use. Although having a pimp or manager can also exacerbate economic vulnerabilities, previous research with primarily streetbased female sex workers in Tijuana found that only 2.7 % reported having a Bpimp^3 and that these women report maintaining autonomy from men in their work, 36 so we do not think that this is a major factor driving this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that socioeconomic conditions often underlie entry into sex work and that economic vulnerability can increase HIV-related risks by reducing women's negotiating power with clients and increasing unprotected sex in exchange for more money. 34,35 FSW-PWID who earn less income may be more vulnerable overall and deeply entrenched in drug use. Although having a pimp or manager can also exacerbate economic vulnerabilities, previous research with primarily streetbased female sex workers in Tijuana found that only 2.7 % reported having a Bpimp^3 and that these women report maintaining autonomy from men in their work, 36 so we do not think that this is a major factor driving this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of these studies examined how supportive venue-based policies 30, 32, 76, 77, 78, 79, 80, 81 or managerial practices (eg, client sign-in, safety mechanisms, or removal of violent clients) 48, 69, 76, 77, 80, 81, 82, 83, 84, 85 and physical features (eg, types or layout of venues) of sex work establishments are associated with increased condom use, often through synergistic effects with other social features of increased peer or sex worker support 32, 52, 53, 69, 72, 76, 79, 81, 83, 85, 86, 87, 88, 89, 90. Work environments for FSWs are shaped by economic features (eg, economic pressures, client financial incentives for non-condom use, refusal of payment, and bribes or fines by state agents [eg, police] to avoid arrest) resulting from macrostructural forces of poverty, laws, and access to resources and are associated with non-condom use27, 28, 29, 30, 40, 41, 48, 64, 70, 83, 84, 87, 91, 92, 93 and HIV infection among FSWs. 36, 65, 75, 94 Conversely, higher income and absence of economic dependence among FSWs mitigate HIV risks, including increased condom use 40, 48, 80, 86, 87 and lower HIV prevalence.…”
Section: Structural Determinants Of Hivmentioning
confidence: 99%
“…14 FSWs from the state experience substantially high rates of physical and sexual violence, which is positively correlated with economic insecurity. 10 Another study has concluded that unstable housing among FSWs is linked to experience of sexual and physical violence and their risky sexual behaviours. 12 Recognising the importance of such structural barriers, researchers have argued that HIV prevention programmes must go beyond the peer-led intervention approach to address the complex social, cultural, political and economic vulnerabilities faced by marginalised population groups most at risk of acquiring HIV infection.…”
Section: Hiv Prevalence Among Indianmentioning
confidence: 99%